29th Digital Avionics Systems Conference 2010
DOI: 10.1109/dasc.2010.5655521
|View full text |Cite
|
Sign up to set email alerts
|

Determination and ranking of trajectory accuracy factors

Abstract: Trajectory accuracy improvements provide the opportunity to reduce fuel consumption and emissions by increasing the predictability of the National Airspace System (NAS). In addition to the environmental benefits, the ability to improve trajectory prediction accuracy enables trajectory based operations (TBO). Because of the foundational reliance on accurate gate-to-gate four dimensional trajectory (4DT) predictions in TBO, trajectory predictors (TP) will have to meet stringent accuracy performance requirements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The top of descent location, speed settings, wind speed, temporary level-offs and vectoring instructions were shown to have a large impact on the prediction errors in the descent phase in the study performed by Mondoloni et al (2005) [13]. Torres (2010) has identified that the velocity effects (most likely wind and speed settings) in the cruise phase and vertical modelling effects in the climb and descent phases are the largest sources of prediction errors [16]. In this study, barring the effect of ATC intent, the wind conditions, the CAS and Mach number speed settings, the vertical speed settings (usually as a function of the aircraft mass and thrust settings), and the temporary level-offs were determined to be the most influential inputs.…”
Section: Relation To Results Of Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The top of descent location, speed settings, wind speed, temporary level-offs and vectoring instructions were shown to have a large impact on the prediction errors in the descent phase in the study performed by Mondoloni et al (2005) [13]. Torres (2010) has identified that the velocity effects (most likely wind and speed settings) in the cruise phase and vertical modelling effects in the climb and descent phases are the largest sources of prediction errors [16]. In this study, barring the effect of ATC intent, the wind conditions, the CAS and Mach number speed settings, the vertical speed settings (usually as a function of the aircraft mass and thrust settings), and the temporary level-offs were determined to be the most influential inputs.…”
Section: Relation To Results Of Previous Researchmentioning
confidence: 99%
“…Much research has been conducted exploring the problem of trajectory prediction uncertainty [9][10][11][12][13][14][15][16][17][18][19][20]. Henderson et al (2013) measured the trajectory prediction accuracy and quantified the sources of errors by conducting field trials, where aircraft were descending at one of three predefined speed profiles [17].…”
mentioning
confidence: 99%
“…64 However, the prediction is never perfect due to several sources of error as presented in. 25 Inaccurate wind information is the major source of aircraft trajectory prediction error.…”
Section: Introductionmentioning
confidence: 98%
“…The first two categories of trajectory error factors are analyzed in [3]. This paper focuses on the trajectory sampling and representation errors.…”
Section: Introductionmentioning
confidence: 99%